Pengaruh Bystander Effect, Profesionalisme dan Pemberian Reward Terhadap Intention Whistleblowing Pada Pemerintah Kota Padang - Hessa, Ar Razaaq Roofiq; Helmayunita, Nayang (Universitas Negeri Padang, 2025)
This research discusses the influence of bystander effect, profesionalisme, and reward giving on intention whistleblowing. This research uses a quantitative approach. This research population is Regional Apparatus Orgabization (OPD) of Padang City. The sampling method in this research used total sampling. So that all OPD will be the research sample. The respondent that have been determined by researchers in this study are the head of the OPD and three sub-division employees of each OPD who work in the financial sector. So the researchers will submit 4 questionnaires to 40 OPD. Based on the results of statistical tests, bystander effect and reward giving have no influence on intention whistleblowing, while profesionalisme has an effect on the intention whistleblowing.